Schedule Pressure in Construction Projects in Nepal - KC, Prabhat (Journal of Advanced Academic Research, 2015)
Accelerating project can be rewarding. The consequences, however, can be troublesome if productivity and quality are sacrificed for the sake of accelerating the schedule. The trade-off among schedule pressure and its causes and effects are often overlooked when schedule decisions are being made. Altogether 68 respondents including owners, consultants, contractors, supervisors and workers were purposively selected from ten construction projects in Nepal. The perception level of schedule pressure and their agreement on twenty hypothesized statements were gathered for the study. Result shows that major drawbacks of schedule pressure are working out of sequence, generating defective works, wastage of materials, increasing construction costs, cutting corners, and losing the motivation to work; and thus generating claims and disputes. Adverse effects of schedule pressure can be minimized by scheduling construction activities realistically and planning them proactively, motivating workers, and establishing the effective project coordination and communication mechanism. Journal of Advanced Academic Research Vol.1(1) 2014: 76-84